2006
DOI: 10.1093/ajcn/83.4.895
|View full text |Cite
|
Sign up to set email alerts
|

Folate intake, alcohol use, and postmenopausal breast cancer risk in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial

Abstract: Our results do not support the hypothesis that high folate intake reduces breast cancer risk; instead, they suggest that a high intake, generally attributable to supplemental folic acid, may increase the risk in postmenopausal women. However, our results confirm previous studies showing positive associations between moderate alcohol consumption and breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
164
2
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(186 citation statements)
references
References 39 publications
(72 reference statements)
8
164
2
9
Order By: Relevance
“…18 There is also evidence to suggest that folic acid supplementation increases the risk of breast cancer in postmenopausal women. 19 Whether these are true associations or epiphenomena requires further study, but nevertheless highlights the complexity of the one-carbon folate pathway and its interaction with carcinogenesis.…”
Section: Neural Tubule Defectsmentioning
confidence: 99%
“…18 There is also evidence to suggest that folic acid supplementation increases the risk of breast cancer in postmenopausal women. 19 Whether these are true associations or epiphenomena requires further study, but nevertheless highlights the complexity of the one-carbon folate pathway and its interaction with carcinogenesis.…”
Section: Neural Tubule Defectsmentioning
confidence: 99%
“…6 Although a meta-analysis did not support the protective effect of folate intake on breast cancer risk, 7 a significant interaction between alcohol and folate intake has been reported for breast cancer. [8][9][10][11][12][13] Given that proliferative benign breast disease (BBD) is associated with risk of subsequent invasive breast cancer, 14,15 the associations between intakes of alcohol and folate and the risk of proliferative BBD could have implications for the prevention of breast cancer. The results of epidemiologic studies of alcohol consumption and proliferative BBD have been inconsistent or even conflicting.…”
mentioning
confidence: 99%
“…17 In addition, 3 cohort studies reported that the risk of invasive breast cancer associated with recent alcohol consumption did not significantly vary with recent folate intake, [30][31][32] although 8 cohort studies showed stronger positive associations between recent alcohol consumption and the risk of invasive breast cancer in women who had low folate intake or circulating folate concentrations versus women with high folate intake or circulating folate concentrations. [8][9][10][11][12][13]33 Despite the critical role of folate in gene expression and DNA repair, the reported relationship between folate intake or circulating folate levels and breast cancer risk has been inconsistent. 7 Our study provides no evidence for a protective effect of folate intake during adolescence on risk of proliferative BBD.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although a meta-analysis did not support the protective effect of folate intake on breast cancer risk, 7 a significant interaction between alcohol and folate intake has been reported for breast cancer. [8][9][10][11][12][13] Given that proliferative benign breast disease (BBD) is associated with risk of subsequent invasive breast cancer, 14,15 the associations between intakes of alcohol and folate and the risk of proliferative BBD could have implications for the prevention of breast cancer. The results of epidemiologic studies of alcohol consumption and proliferative BBD have been inconsistent or even conflicting.…”
mentioning
confidence: 99%